METHOD FOR FORMING TEST WORKFLOW BASED ON FUZZY INFERENCE - Shytikova, O. V.; Tabunshchyk, S. S.; Tabunshchyk, G. V. (Radio Electronics, Computer Science, Control, 2018)
Actuality. Test process costs can be reduced by rational planning of all works and the optimal allocation of the resources. One of the main documents which regulate the purpose and tasks of the test process, its’ scope, procedure and methods of carrying out the work, is a test program. The process of it creation is represented as a sequence of interrelated tasks. In the view of the high costs of material and non-material resources, the improvement of the testing is possible due to a reasonable choice of scope of work and controlled variables. The object of the research – the test process of the compound technical system. The subject of the research – the method for collection and analysis of controlled parameters within test process of the compound technical system. Goal of the research is to develop a method for forming the scope of testing workflows which will be included in the compound technical system test program. Method. A method for forming of the testing workflows scope for a test program for compound technical systems is developed by the authors. It is based on a combination of direct logical inference for the formation of a set of monitored parameters and a fuzzy logical conclusion for the composition of works that are expedient for one launch of the compound technical systems. Combination of different work types reduces direct costs and reduces the test process cost. Results. Developed method was used for the tests of the gas turbine unit for terrestrial usage. According to the test costs classification, usage of the suggested approach for forming test process workflows reduced labor costs, capital (materials) resources and alternative resources, due to the reducing of experiments number for a gas turbine power station. Conclusions. Method for workflows forming for test program of compound technical systems allows combining working processes, which are possible to run within one launch of the technical system. The application of the method has reduced test process costs by reducing time and man-hour for creation of test program, as well as reducing number of launches of the gas turbine unit, with the increase of work scope for one launch.